Predictive Value of Serum Progesterone Levels on The Day of Frozen-Thawed Embryo Transfer in Determining Pregnancy Outcomes in Infertile Women: A Cohort Prospective Study - Saeideh Dashti; Nasim Tabibnejad; Farimah Shamsi; Behnaz Gandom (International Journal of Fertility and Sterility)
Background: Hormone replacement therapy (HRT) is the preferred protocol for endometrial preparation. Progesterone is important for successful implantation and the outcome of assisted reproductive techniques (ART). The impact of serum progesterone concentration on pregnancy outcomes has been extensively studied; however, there are conflicting results for dosage and route of administration. This study investigates the association between serum progesterone levels on embryo transfer day and assisted reproductive technique outcomes in frozen-thawed embryo transfer (FET).Materials and Methods: This prospective cohort study was conducted on women who underwent FET. Participants received HRT with 6 mg of oestradiol valerate and 400 mg of micronized vaginal progesterone, along with 50 mg of intramuscular (IM) progesterone for endometrial preparation. Serum progesterone was assessed before embryo transfer. The primary outcome was live birth rate (LBR).Results: Overall, 190 infertile women underwent cleavage FET and were categorised according to the presence (group I: n=38) or absence (group II: n=152) of live birth. Group I women had significantly higher progesterone levels on the transfer day (34.48 ± 8.95 ng/ml) compared to group II women (29.83 ± 11.076 ng/ml, P=0.008). We divided the serum progesterone values into quartiles and observed significantly lower clinical pregnancy rates in the Q1 quartile (progesterone ≤23.84 ng/ml). Receiver operating characteristic (ROC) curve analysis indicated a significant threshold for progesterone level on the day of embryo transfer in terms of LBR, with an area under the curve (AUC) of 0.64 [95% confidence interval (CI): 0.54-0.73, P<0.001]. The estimated threshold was 26.95 ng/ml, with a sensitivity of 82% and a specificity of 43%.Conclusion: The present study showed a significant positive association between serum progesterone levels on transfer day and LBR in FET cycles after patients received a combination of vaginal and IM progesterone supplements. Monitoring of serum progesterone in FET cycles are recommended.